2022
DOI: 10.1021/acsomega.2c05449
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Filtration Performance of Solution Blown PA6 Webs with Bimodal Fiber Distribution

Abstract: A bimodal web, where both nanofibers and microfibers are present and distributed randomly across the same web, can deliver high filter efficiency and low pressure drop at the same time since in such a web, filter efficiency is high thanks to small pores created by the presence of nanofibers and the interfiber space created by the presence of microfibers, which is large enough for air to flow through with little resistance. In this work, a bimodal polyamide 6 (PA6) filter web was fabricated via a modified solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…A bimodal approach is being studied to obtain low pressure drop values by increasing the filtration efficiency of filter mats. The nanofibers mixed between the microfibers on the surfaces formed by combining micro and nanofibers with bimodal filter mats increase the filtration efficiency by creating new air channels and prevent the pressure drop from increasing [12,13]. In the study conducted by Lin et al, it was revealed that a bimodal filter showed a high filtration performance (98.43%) when the average fiber diameters were 2.44 and 0.13 μm,…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…A bimodal approach is being studied to obtain low pressure drop values by increasing the filtration efficiency of filter mats. The nanofibers mixed between the microfibers on the surfaces formed by combining micro and nanofibers with bimodal filter mats increase the filtration efficiency by creating new air channels and prevent the pressure drop from increasing [12,13]. In the study conducted by Lin et al, it was revealed that a bimodal filter showed a high filtration performance (98.43%) when the average fiber diameters were 2.44 and 0.13 μm,…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…Furthermore, a study that combined microfibers and nanofibers obtained via melt/solution electrospinning of polyamide (PA) achieved a notable 98% filtration efficiency with a ΔP of 50 Pa at a speed of 5.3 cm/s, specifically for PM 2.5 20 . In another investigation, a bimodal filter comprising average 81 nm and 1.6 μm diameter fibers was produced by simultaneously blowing PA fibers from solutions with different concentrations, resulting in an impressive 98.891% filtration efficiency and a ΔP of 168 Pa at a face velocity of 15.83 cm/s 21 …”
Section: Introductionmentioning
confidence: 99%
“…20 In another investigation, a bimodal filter comprising average 81 nm and 1.6 μm diameter fibers was produced by simultaneously blowing PA fibers from solutions with different concentrations, resulting in an impressive 98.891% filtration efficiency and a ΔP of 168 Pa at a face velocity of 15.83 cm/s. 21 The electrostatic charge in filters plays a vital role in particle capture with high efficiency and low ΔP. The charging process involves several charge mechanisms, such as corona charging, contact charging, and induction charging.…”
mentioning
confidence: 99%
“…However, the electret charge is prone to escaping. 12 The combination of microfibers and nanofibers is an effective method for achieving high efficiency and low resistance. This is because the prepared fiber membranes have small pore sizes, high porosity, and universality.…”
Section: Introductionmentioning
confidence: 99%